Intermittent preventive treatment, malaria, HIV, hepatitis and pregnancy outcomes in Nigerian women: a cross-sectional study in two healthcare facilities - Rebecca Chinyelu Chukwuanukwu; George Uchenna Eleje; Felix Emeka Menkiti; Golibe Christian Ikpeze; Chioma Ngozichukwu Mbachu; Nnaedozie Paul Obiegbu; Confidence Chinaza Ogbomade; Hatesin Ifeanyi Anyaegbu; Alfred Friday Ehiaghe; Dorothy Amauche Ezeagwuna; Chidi Callistus Efobi; Emmanuel Chukwubuikem Egwuatu; et al. (BMC Pregnancy and Childbirth)
Abstract Background Malaria infection during pregnancy remains a public health concern. Malaria prevention strategies, including chemoprevention, are recommended during pregnancy. This study was conducted to assess the use of intermittent preventive treatment for malaria during pregnancy (IPTp), the prevalence of malaria, HIV, and hepatitis infections and the occurrence of premature rupture of membranes (PROM) among pregnant women in two healthcare facilities in south-eastern Nigeria. Methods A dual hospital-based cross-sectional study was conducted in two hospitals in Anambra State, Nigeria. Pregnant women who provided informed consent were recruited. Blood samples were collected to test for HIV, malaria, hepatitis B and C virus infections. Results Among the 134 participants enrolled, 8 (5.97%) tested positive for malaria, 5 (3.73%) for HIV, and 6 (4.47%) for hepatitis B; preeclampsia was observed in 5 women (3.73%), and 3 (2.24%) experienced PROM. The use of IPTp was relatively high at 73.9%. Preterm deliveries accounted for 5.2% of the cases. Conclusion A lower prevalence of malaria was observed in this study than in previous reports in the region, likely due to the high implementation of IPTp. These findings emphasize the role of IPTp in reducing malaria among pregnant women and provide useful data on HIV, hepatitis and PROM prevalence in the study population.